The impact of boron atoms on clathrate-I silicides: composition range of the borosilicide K8−xBySi46−y. Issue 4 (4th January 2021) - Jung, Walter; Böhme, Bodo; Hübner, Julia M.; Burkhardt, Ulrich; Borrmann, Horst; Bobnar, Matej; Nguyen, Hong Duong; Pantenburg, Ingo; Etter, Martin; Schwarz, Ulrich; Grin, Yuri; Baitinger, Michael
Abstract : The clathrate-I borosilicide K8− x B y Si46− y (0.8 ≤ x ≤ 1.2 and 6.4 ≤ y ≤ 7.2; space group Pm 3̄ n ) was prepared in sealed tantalum ampoules between 900 °C and 1000 °C. Abstract : The clathrate-I borosilicide K8− x B y Si46− y (0.8 ≤ x ≤ 1.2 and 6.4 ≤ y ≤ 7.2; space group Pm 3̄ n ) was prepared in sealed tantalum ampoules between 900 °C and 1000 °C. By high-pressure preparation at 8 GPa and 1000 °C, a higher boron content is achieved ( x = 0.2, y = 7.8). Crystal structure and composition were established from X-ray diffraction data, chemical analysis, WDX spectroscopy, and confirmed by 11 B and 29 Si NMR, and magnetic susceptibility measurements. The compositions are electron-balanced according to the Zintl rule within one estimated standard deviation. The lattice parameter varies with composition from a = 9.905 Å for K7.85(2) B7.8(1) Si38.2(1) to a = 9.968(1) Å for K6.80(2) B6.4(5) Si39.6(5) .